1992
DOI: 10.1111/j.1432-1033.1992.tb16684.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro studies of the purine‐cytosine permease of Saccharomyces cerevisiae

Abstract: The FCY2 gene of the purine-cytosine permease (PCP) of Saccharomyces cerevisiae and the allele fcy2-21 have been cloned on the yeast multicopy plasmid pJDB207. The corresponding plasmids were introduced into a S. cerevisiur strain carrying a chromosomal deletion at the FCY2 locus. The resulting strains were designated pAB4 and pAB25 respectively. The pAB25 strain, which carries the fcy2-21 allele, contains four amino acid changes in the open reading frame of the PCP (Weber et al., 1989). The influence of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…Activity Measurements on CL-PMV-Ligand equilibrium binding measurements were performed at 4°C on CL-PMV by a centrifugation technique as already described (26) in K ϩ buffer, pH 5.7, containing NaCl (100 mM) and [2-14 C]cytosine (620 MBq⅐mmol…”
Section: Measurements Of Transmembrane Electric Potential and Phmentioning
confidence: 99%
“…Activity Measurements on CL-PMV-Ligand equilibrium binding measurements were performed at 4°C on CL-PMV by a centrifugation technique as already described (26) in K ϩ buffer, pH 5.7, containing NaCl (100 mM) and [2-14 C]cytosine (620 MBq⅐mmol…”
Section: Measurements Of Transmembrane Electric Potential and Phmentioning
confidence: 99%
“…It has been shown that the 4 bases bind to the same site with very similar affinities and that their uptake occurs with equivalent efficencies (3,9). To identify the binding site, an interesting approach involves the isolation of mutant strains with altered affinity constants for the various ligands, as already described in the case of lactose permease of Escherichia coli (10 -12).…”
mentioning
confidence: 99%
“…All these mutants displayed modifications of the uptake parameters for the different bases. We have already extensively described the triple mutant strain and shown that modifications of equilibrium binding parameters were responsible for the uptake phenotype (9).…”
mentioning
confidence: 99%
“…[ 14 C]uracil uptake transport was abolished in the fur4⌬ mutant but not in the dal4⌬ mutant, indicating that Fur4p specifically transported uracil. In wild-type strains of S. cerevisiae, the kinetic parameters of the transport of cytosine by Fcy2p and uracil by Fur4p are very similar, with Kt app values around 2 M and V max values in the range of 8 to 10 nmol/min/10 7 cells (16,28). In the C. lusitaniae wild-type strain, Fcy2p shows a greater affinity for cytosine [Kt app , 6 M] (8) than Fur4p for uracil [Kt app , 20 to 24 M], which itself has 10 times less affinity for uracil than Fur4p of S. cerevisiae (2.5 M) (16).…”
Section: Discussionmentioning
confidence: 99%